2019
DOI: 10.2478/foecol-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Some ecological aspects of dhole (Cuon alpinus) in the Huai Kha Khaeng Wildlife Sanctuary, Uthai Thani Province, Thailand

Abstract: The dhole (Cuon alpinus) is one of the least frequent studied endangered canid species and many aspects of ecological knowledge about this species are lacking. The objectives of this study were to investigate the spatial movement of dholes, prey abundance, prey selection, and prey overlaps with other large carnivorous species in the Huai Kha Khaeng Wildlife Sanctuary, Thailand, during November, 2017 and October, 2018. Two adult female dholes were captured and fitted with GPS collars. Twenty camera trap sets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The average activity period of dholes is 14:49 hours, and mostly diurnal. The average activity period of dholes is not significant difference when compared with the period of dholes in Huai Kha Khaeng Wildlife Sanctuary located in the western part of the country (11:17 hours 169.397°, n=22) (Charaspet et al 2019) and Khao Ang Rue Nai Wildlife Sanctuary (10:41 hours 160.354°, n=732) (Ruengtik et al 2019) located in the eastern part of Thailand (Hotelling's Test (F) = 9.273, P=0.226). That confirms the activity period of dholes in Thailand mostly occur during day time.…”
Section: Discussionmentioning
confidence: 76%
“…The average activity period of dholes is 14:49 hours, and mostly diurnal. The average activity period of dholes is not significant difference when compared with the period of dholes in Huai Kha Khaeng Wildlife Sanctuary located in the western part of the country (11:17 hours 169.397°, n=22) (Charaspet et al 2019) and Khao Ang Rue Nai Wildlife Sanctuary (10:41 hours 160.354°, n=732) (Ruengtik et al 2019) located in the eastern part of Thailand (Hotelling's Test (F) = 9.273, P=0.226). That confirms the activity period of dholes in Thailand mostly occur during day time.…”
Section: Discussionmentioning
confidence: 76%
“…By studying the types of leopard food in Huai Kha Khaeng Wildlife Sanctuary, Simcharoen (2008) reported that 27 types of prey were found from scat analysis with the respective highest frequencies of occurrence were sambar deer, Malayan porcupine, wild boar, red muntjac, banteng, Phayre's langur (Trachypithecus phayrei), crabeating macaque (Macaca fascicularis), white-handed gibbon (Hylobates lar), Bengal slow loris (Nycticebus bengalensis), and rhesus macaque (Macaca mulatta). Pianka's prey overlap index between dhole and leopard preys acquired from data collection in the same time period in Huai Kha Khaeng Wildlife Sanctuary was 0.98 and the index between dhole and tiger was 0.68 (Charaspet et al 2019). Ramesh et al (2012) found that dhole separated the habitat on a temporal basis with tiger and leopard in the same area without any overlap.…”
Section: Introductionmentioning
confidence: 95%
“…There is concentrated interaction between large carnivores and their preys in Huai Kha Khaeng Wildlife Sanctuary. Charaspet et al (2019) reported that the habitat area of female dhole in the sanctuary studied from satellite radiofrequency was 34 km 2 . Phetdee (2000) studied the prey species of large carnivores in the sanctuary and reported that there were 18 tiger prey species found using scat analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The overlap index between Leopard and Tiger was 0.90 when using the results of prey species found in Leopard scats from the study of Simchareon (2008) and research results of prey species of tiger from the study of Phetdee (2000). However, Charaspet et al (2019) reported that the overlap index between prey of Dhole and Leopard found between data collection process in HKKWS was 0.98. The overlap index between Dhole and Tiger was 0.68 which was higher than the result of this study.…”
Section: Dietary Diversity Index Niche Breadth Index and Pianka Preymentioning
confidence: 96%
“…The absence of Wild boar in any scats found in HKKWS is also consistent with the study of Kamler et al (2012;2020) which reported that Dholes avoided consuming Wild boar by considering prey electivity index. Charaspet et al (2019) reported that Pianka's prey overlap index for Dhole and Leopard received from data collection in HKKWS pointed out the fierce competition in the area. That makes Dholes in the area it is less abundant than Tigers and Leopards and consumed smaller prey in Viverrid species and Malayan porcupines.…”
Section: Electivity Indexmentioning
confidence: 99%